Mental Representations of Emotional Systems in the Poetry of Ayash Yahyaoui - hamdaoui, asma (El Omda in Linguistics and Discourse Analysis, 2022)
This research study aims to shed light on the passions in the poetry discourse of the Algerian poet 'AYYASH YAHYAOUI" in its relationships with the cognitive and psychological approaches.